Chlorophyll „a” measurement as an index of phytoplankton bloom and primary production in the Gulf of Guinea, Nigeria, West Africa - KADIRI, Medina Omo; OGBEBOR, Jeffrey Uyi; OMORUYI, Osasere Abike; UNUSIOTAME-OWOLAGBA, Timothy (Studia Universitatis Babeș-Bolyai Biologia, 2019)
Chlorophyll a levels of oceanic waters in Nigeria located in the Gulf of Guinea and adjoining water bodies were investigated in this study. Sample collections were done at quarterly intervals from March 2014 to January 2015 from fifty-five sites and spanned over eight coastal states. Integrated water sample for chlorophyll analysis was taken from a depth of 10m to the surface using a silicone hose. Determination of chlorophyll was done by a combination of filtration, extraction, homogenization, centrifugation and spectrophotometry using the trichromatic method. The range of chlorophyll a concentration was 27.5 – 1419.35 µgL-1 in oceanic waters and 32.79 – 1649.64 µgL-1 in adjoining water bodies. Chlorophyll a concentrations varied spatially and temporally, with a general observation of higher concentrations in the south-west oceanic locations in the Bight of Benin axis of the Gulf of Guinea, compared to the south-south oceanic locations in the Bight of Bonny axis of the Gulf of Guinea In the adjoining coastal waters, the Gbaji River in Badagry, Lagos, located in the South-West, had the highest overall total chlorophyll a concentration while the Brass River in Bayelsa, located in the South-South had the lowest overall total chlorophyll a concentration throughout the study period. The mean primary production, ranging from 439.85 µgL-1 to 1051.89 µgL-1, were included in six categories of <500 µgL-1; 600-699 µgL-1; 700-799 µgL-1; 800-899 µgL-1; 900-999 µgL-1 and >1000 µgL-1. Principal component analysis showed strong positive correlations of chlorophyll a with total biomass of major phytoplankton groups (Bacillariophyta, Dinophyta and Cyanophyta) and dissolved oxygen levels; negative correlation of chlorophyll a with Fe, NO3, PO4, TDS, SiO3 and turbidity.